Conversations About Opioids: Impact of the Opioid Overdose Epidemic on Social Interactions for People Who Live With Chronic Pain. (July 2021) - Dassieu, Lise; Heino, Angela; Develay, Élise; Kaboré, Jean-Luc; Pagé, M. Gabrielle; Hudspith, Maria; Moor, Gregg; Choinière, Manon
The objective of this study was to understand the impact of the opioid overdose epidemic on the social lives of people suffering from chronic pain, focusing on interactions within their personal and professional circles. The study was based on 22 in-depth interviews with people living with chronic pain in Canada. Using thematic analysis, we documented three main impacts of the opioid overdose epidemic: (a) increased worries of people in pain and their families regarding the dangers of opioids; (b) prejudices, stigma, and discrimination faced during conversations about opioids; and (c) stigma management attempts, which include self-advocacy and concealment of opioid use. This study represents important knowledge advancement on how people manage stigma and communicate about chronic disease during everyday life interactions. By showing negative effects of the epidemic's media coverage on the social experiences of people with chronic pain, we underscore needs for destigmatizing approaches in public communication regarding opioids.